Rural (Village) Finance Management and Its Effect on Unlawful Misconduct - Soesanto, Heri; Sudarsono, Sudarsono; Ridwan, Ridwan; Winarno, Bambang (Acta Universitatis Danubius. Juridica, 2023)
The purpose of this research is to understand and explore village financial management after the Law of the Republic of Indonesia Number 6 of 2014 on Villages which has implications for unlawful acts. This research method uses this research, referring to the type of research on normative research. The specificity of this normative research is based on finding the truth of coherence, namely a truth based on the suitability between what is studied and the rules applied in village financial management, which have criminal implications. The research result show after the village financial management law of the Republic of Indonesia Number 6 of 2014 concerning villages that contain the potential for criminal acts of corruption occurred in: First, the Allocation of Village Funds; Second, the source of Grant Financing; Third, Village Original Income Sources; Fourth, other sources of village income. The conclusion is after the Law on Village Financial Management of the Republic of Indonesia Number 6 of 2014 concerning Villages with Implications for unlawful acts. Generally, in the form of abuse of authority by the village head and village officials as village financial managers, this happened due to several things: first, the determination of wetmatigheid, rechtmatigheid, and doelmatigheid.